Pengaruh Self Assesment System Terhadap Kepatuhan Wajib Pajak - S Mia Lasmaya; Neni Nur Fitriani (STMIK Mardira Indonesia, Bandung, 2017)
The purpose of this study is to know the implementation of self assessment system of private person, to know Personal Taxpayer Compliance in one of KPP in Bandung and to know how much influence Self assessment system to Personal Taxpayer Compliance. The method used in research on one KPP Pratama in Bandung is descriptive analysis method where the technique used in collecting data is done through interviews, questionnaires and library research, Sampling technique with nonprobability sampling is a saturated sample, where all members of the population are sampled and techniques data analysis is done through descriptive analysis and verification analysis. Based on the results obtained the self assessment system is in the category good enough and for Personal Taxpayer Compliance is in the category quite well. Self assessment system has an effect on Personal Taxpayer Compliance of 46,0%, while the rest 54,0% influenced by other factors not examined in this research like condition of tax administration system, service at taxpayer, enforcement of tax law, tariff taxes and so forth. Thus it can be concluded that the influence of self assessment system on taxpayer compliance of individuals on one KPP Pratama in Bandung. Keywords: self assessment system, personal taxpayer compliance.